Regulation of Privacy Policies: A Perspective from Public Law Protection of Personal Information - Zhao, Xiangrui (International Journal of Social Sciences and Public Administration, 2025)
Online platforms process personal data through privacy policies while pledging to protect users’ personal information. Although derived from traditional privacy concepts, privacy policies differ significantly in nature-personal information protection carries stronger public law attributes, rendering privacy policies primarily compliance instruments that should integrate both self-regulation and government regulation approaches. With the rapid expansion of platforms’ private power, privacy policies, despite their enhanced role, have exhibited alienating effects: failures in self-regulation, erosion of user rights, and circumvention of governmental oversight. To address these issues, a meta-regulatory approach is imperative, requiring tripartite collaboration among platforms, users, and regulatory authorities to refine privacy policy frameworks.